The giver - LOWRY, LOIS; LOIS LOWRY (New York Dell Laurel-Leaf, 1993)
a dystopian novel about 12-year-old Jonas, who lives in a "utopian" society free of pain, color, and emotion, managed by "Sameness".
Keywords: profound wisdom, and the heavy burden of holding humanity's collective memories; a life without pain, conflict, or freedom is not truly worth living, as it requires sacrificing love, joy, and humanity